Pengembangan Modul IPA Berbasis Kearifan Lokal Batik Gajah Oling Banyuwangi Pada Materi Klasifikasi Tumbuhan Untuk Siswa SMP/MTs - Elly Purwandari; Rafiatul Hasanah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
The purpose of this study was to describe the validity and response of students to the local wisdom-based science module Batik Gajah Oling Banyuwangi on plant classification material for SMP/MTs students. This type of research is development research (RD) with Thiagarajan's 4D model. The subjects for this trial were 30 students of class VII MTsN 8 Banyuwangi. The data collection instrument used was a validation questionnaire from experts and a small and large scale trial questionnaire for students. Validation from experts as well as small and large scale trials were carried out to determine the validity and student responses to the IPA module based on local wisdom of Gajah Oling Banyuwangi batik on plant classification material. The results obtained from the data collection were that the developed module received a score of 94.78% from the experts, for small-scale trials it received a value of 96.6%, and large-scale trials received a value of 91.5%. From these results it can be seen that the IPA module based on the local wisdom of Gajah Oling Banyuwangi batik on the plant classification material that the researchers developed has entered the